2017
DOI: 10.26480/msp.01.2017.12.16
|View full text |Cite
|
Sign up to set email alerts
|

Lipid lowering effect of synthetic phenolic compound in a high- fat diet (HFD) induced hyperlipidemic mice

Abstract: Hyperlipidemia is the major risk factor of arteriosclerosis, coronary heart diseases and death. Phenolic compounds have been shown to offer the protection against cardiovascular complications. In the present study, we studied the effect of semisynthetic phenolic compounds on the hyperlipidemic mice fed with high fat diet (cholesterol, cholic acid and peanut oil). Phenolic compounds were mixed with HFD and the dose of the test compounds were 1 0mg/kg for 6 weeks. After 6 weeks, the average body weight of lab di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 5 publications
(2 reference statements)
0
12
0
Order By: Relevance
“…The three-good extraction yield of berberine were achieved by hydrochloric acid/methanol-ultrasonic, hydrochloric acid/distilled water-ultrasonic and hydrochloric acid/ethanol-ultrasonic. The three-good extraction yield of palmatine were achieved hydrochloric acid/ethanol-ultrasonic, hydrochloric acid/methanol-ultrasonic and hydrochloric acid/methanol-Soxhlet (Nawaz et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…The three-good extraction yield of berberine were achieved by hydrochloric acid/methanol-ultrasonic, hydrochloric acid/distilled water-ultrasonic and hydrochloric acid/ethanol-ultrasonic. The three-good extraction yield of palmatine were achieved hydrochloric acid/ethanol-ultrasonic, hydrochloric acid/methanol-ultrasonic and hydrochloric acid/methanol-Soxhlet (Nawaz et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…In previous report, significant body weight gain compared with control was considered as criteria of successfully constructed obese mice model [ 2 , 20 ]. While HFD induced body weight increase, significantly higher body weight than control is not always consistence with obesity and its relevant symptoms [ 28 ]. It was found that HFD induced obesity in C57BL/6J and BALB/c mice, which are obesity prone mice sub-strain of C57BL/6 and BALB/c respectively, and increased their body weight.…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes mellitus has become a global problem in recent decades: it is a leading cause of blindness, end stage renal disease and non-traumatic amputation. Its prevalence increased day by day worldwide without any plateau ( Spanou and Tziomalos, 2013 , Nawaz et al, 2017a , Nawaz et al, 2017b ). So, there is need of healthy natural products to cure this disease ( Abbas et al, 2017 , Gohar et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%